Trade-off between antibacterial immune defense and oogenesis progression in female Drosophila melanogaster. - Gordon, K.E.; Ray, S.; Marcin, J.M.; Gonzales, P.M.; Li, M.L.; Liang, C.; Wolfner, M.F.; Lazzaro, B.P. (Genetics, 2025)
Trade-offs between reproduction and immunity are common in animals, potentially due to preferential allocation of limiting resources. In Drosophila melanogaster, mating stimulates egg production but also triggers a rapid and persistent decrease in female immune defense. Proteins essential for both processes are produced in fat body tissue, which may result in competition for cellular resources that could drive a functional trade-off between reproduction and immune defense. We predicted that arrest of oogenesis prior to egg provisioning would alleviate postmating immune suppression because cellular stress would be relieved, but that postmating immune suppression would be observed in genotypes that fully provision eggs even if fertility is compromised. In the present study, we test these predictions by evaluating postmating immune competence in mated D. melanogaster mutants that arrest oogenesis either prior to, or subsequent to, vitellogenesis. Consistent with our prediction, we find that mated female immune defense is maintained when egg development is arrested prior to vitellogenesis. We find that progression through the vitellogenic stages of oogenesis results in postmating immune suppression, except in the case of a mutant with an egg-retention phenotype, where we infer that the failure to lay eggs results in feedback that inhibits subsequent egg development. We additionally show that elimination of yolk protein synthesis in the fat body and follicle cells of the ovary partially restores female immune capacity. Nevertheless, females that lack yolk protein genes still experience partially reduced immune capacity after mating, suggesting that other reproductive demands also suppress immune defense.